Faktor Mempengaruhi Dismenore Dengan Metode Kompres Hangat Terhadap Penurunan Nyeri Menstruasi (Dismenore) Lingk X Kel. Suka Maju Kec. Medan Johor Tahun 2023 - Damayanty S; Ade Rachmat Yudianto; Marta Armita Silaban; Ika Damayanti Sipayung (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Adolescents are residents in the age range of 10-18 years, while according to the Population and Family Planning Agency (BKKBN) the age range for adolescents is 10-24 years and unmarried. According to the 2010 population census, the age group of 10-19 years in Indonesia was 43.3 million or around 18% of the total population. In the world, it is estimated that there are 1.2 billion adolescents or 18% of the world's population (WHO, 2014). The type of research used in this study was a quantitative study with a cross-sectional study design with the aim of knowing the factors influencing dysmenorrhea by giving warm compresses to reducing menstrual pain (dysmenorrhea) in a circle x class. like to go forward kec. johor field in 2023. Research location in Lingk X Kel. Like forward, Kec. Medan, Johor, North Sumatra. The number of samples is 45 teenagers. Univariate and Bivariate data analysis. The results showed that there was a significant relationship between knowledge using the warm compress method. which is supported by analysis using Chi Square, P.Value = 0.004 and ? = 0.05, P.Value (0.004) < ? (0.05). Menarche using the warm compress method. which is supported by analysis using Chi Square, P.Value = 0.002 and ? = 0.05, P.Value (0.002) < ? (0.05)